Palindrome-Mediated Translocations in Humans: A New Mechanistic Model for Gross Chromosomal Rearrangements - Inagaki, Hidehito; Kato, Takema; Tsutsumi, Makiko; Ouchi, Yuya; Ohye, Tamae; Kurahashi, Hiroki (Frontiers in Genetics, 2016)
Palindromic DNA sequences, which can form secondary structures, are widely distributed in the human genome. Although the nature of the secondary structure—single-stranded “hairpin” or double-stranded “cruciform”—has been extensively investigated in vitro, the existence of such unusual non-B DNA in vivo remains controversial. Here, we review palindrome-mediated gross chromosomal rearrangements possibly induced by non-B DNA in humans. Recent advances in next-generation sequencing have not yet overcome the difficulty of palindromic sequence analysis. However, a dozen palindromic AT-rich repeat (PATRR) sequences have been identified at the breakpoints of recurrent or non-recurrent chromosomal translocations in humans. The breakages always occur at the center of the palindrome. Analyses of polymorphisms within the palindromes indicate that the symmetry and length of the palindrome affect the frequency of the de novo occurrence of these palindrome-mediated translocations, suggesting the involvement of non-B DNA. Indeed, experiments using a plasmid-based model system showed that the formation of non-B DNA is likely the key to palindrome-mediated genomic rearrangements. Some evidence implies a new mechanism that cruciform DNAs may come close together first in nucleus and illegitimately joined. Analysis of PATRR-mediated translocations in humans will provide further understanding of gross chromosomal rearrangements in many organisms.